2020
DOI: 10.1111/ecog.04423
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating physiology into species distribution models moderates the projected impact of warming on selected Mediterranean marine species

Abstract: Species distribution models (SDMs) correlate species occurrences with environmental predictors, and can be used to forecast distributions under future climates. SDMs have been criticized for not explicitly including the physiological processes underlying the species response to the environment. Recently, new methods have been suggested to combine SDMs with physiological estimates of performance (physiology‐SDMs). In this study, we compare SDM and physiology‐SDM predictions for select marine species in the Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 87 publications
3
62
2
Order By: Relevance
“…However, there is less evidence of the invasive capacity of H. decipiens, as this species was just recently found for the first time in 2018 along the coast of Greece (38 • N) (Gerakaris et al, 2020). Our hindcast model was implemented using only SST, while our SDMs were implemented with only one additional environmental parameter (SST and surface salinity) (i.e., Chefaoui et al, 2018;Wilson et al, 2019;Gamliel et al, 2020). Temperature and salinity are some of the main factors defining the physiological thresholds and distribution of seagrasses (Lee et al, 2007;Marbà and Duarte, 2010), although, other factors (biochemical, physical and biological) may also contribute to determining seagrass habitat ranges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is less evidence of the invasive capacity of H. decipiens, as this species was just recently found for the first time in 2018 along the coast of Greece (38 • N) (Gerakaris et al, 2020). Our hindcast model was implemented using only SST, while our SDMs were implemented with only one additional environmental parameter (SST and surface salinity) (i.e., Chefaoui et al, 2018;Wilson et al, 2019;Gamliel et al, 2020). Temperature and salinity are some of the main factors defining the physiological thresholds and distribution of seagrasses (Lee et al, 2007;Marbà and Duarte, 2010), although, other factors (biochemical, physical and biological) may also contribute to determining seagrass habitat ranges.…”
Section: Discussionmentioning
confidence: 99%
“…The aims of the present study were to (i) improve our understanding of the trait distance and relatedness between H. stipulacea and H. decipiens populations from the Mediterranean Sea and other worldwide populations, (ii) assess whether increases in SST over the last 100 years in the Mediterranean Sea could partially explain the colonization of H. stipulacea in this basin, and finally, (iii) examine the potential habitat expansion of H. stipulacea and H. decipiens in the Mediterranean basin during this century by implementing Species Distribution Models (SDMs) in relation to SSTs and salinities. SDMs have been widely applied to investigate the potential biogeographical shifts in response to the effects of global environmental changes of native and invasive terrestrial and aquatic species, including seagrass (i.e., Valle et al, 2014 ; Chefaoui et al, 2018 ; Beca-Carretero et al, 2020b ; Gamliel et al, 2020 ). Here, we hypothesize that a wide potential expansions of the habitat suitability of H. stipulacea and to a lesser degree of H. decipiens are expected to occur during this century as the Mediterranean Sea becomes warmer and saltier.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this study also showed that carbon-fixing enzymes were able to function in the presence of intra-cellular salt concentrations in vitro, which is an important adaptive mechanism to salinity variations. Detailed experiments exploring the thresholds of H. stipulacea's hyperand hypo-salinity tolerance need to be conducted and combined with niche models in order to predict if salinity is a limiting factor for the spread of this species (see for example Oscar et al, 2018;Gamliel et al, 2020).…”
Section: Salinity Tolerancementioning
confidence: 99%
“…These models are developed using the knowledge on the current distribution of the studied species (the realized niche) which can be potentially projected in space or time to forecast the species distributions within the invaded ranges within a time frame (Fitzpatrick and Hargrove, 2009;Gallien et al, 2010). Applying SDMs for H. stipulacea (Gamliel et al, 2020) using mean annual bottom temperature and net primary productivity as environmental predictors revealed some interesting patterns (Figure 8). The main result was the striking differences in the predicted suitability of the Mediterranean Sea to support H. stipulacea when the model is based on the native (Figure 8A) vs. invaded (Figure 8B) range occurrences.…”
Section: Native and Invaded Ranges: What Is Coming Next?mentioning
confidence: 99%
See 1 more Smart Citation